Left Atrial Transcriptional Changes Associated With Atrial Fibrillation Susceptibility and Persistence. (February 2015) - Deshmukh, Amrish; Barnard, John; Sun, Han; Newton, David; Castel, Laurie; Pettersson, Gosta; Johnston, Douglas; Roselli, Eric; Gillinov, A. Marc; McCurry, Kenneth; Moravec, Christine; Smith, Jonathan D.; et al.
Abstract : Background—: Prior transcriptional studies of atrial fibrillation (AF) have been limited to specific transcripts, animal models, chronic AF, right atria, or small samples. We sought to characterize the left atrial transcriptome in human AF to distinguish changes related to AF susceptibility and persistence. Methods and Results—: Left atrial appendages from 239 patients stratified by coronary artery disease, valve disease, and AF history (no history of AF, AF history in sinus rhythm at surgery, and AF history in AF at surgery) were selected for genome-wide mRNA microarray profiling. Transcripts were examined for differential expression with AF phenotype group. Enrichment in differentially expressed genes was examined in 3 gene set collections: a transcription factor collection, defined by shared conserved cis -regulatory motifs, a miRNA collection, defined by shared 3′ untranslated region motifs, and a molecular function collection, defined by shared Gene Ontology molecular function. AF susceptibility was associated with decreased expression of the targets of CREB/ATF family, heat-shock factor 1, ATF6, SRF, and E2F1 transcription factors. Persistent AF activity was associated with decreased expression in genes and gene sets related to ion channel function consistent with reported functional changes. Conclusions—: AF susceptibility was associated with decreased expression of targets of several transcription factors related to inflammation, oxidation, and cellular stress responses. In contrast, changes in ion channel expression were associated with AF activity but were limited in AF susceptibility. Our results suggest that significant transcriptional remodeling marks susceptibility to AF, whereas remodeling of ion channel expression occurs later in the progression or as a consequence of AF. Abstract : Supplemental Digital Content is available in the text.